50-річний досвід діагностики та лікування хворих із пухлинами надниркових залоз - Павловський, М. П.; Бойко, Н. І.; Гаврик, Я. І. (Clinical Endocrinology and Endocrine Surgery, 2008)
The results of 50 years experience in making the diagnosis and treatment of 738 patients with tumors of adrenal glands are reported. The patients were from 8 till 78 years old. The clinical features depends from the involvment of the adrenal layer. The results of laboratory test (biochemical features, levels of adrenal hormones), instrumental examinations, the methods of preoperative preparation, postoperative complications and long-term follow-up were analyzed. We learned the advantages of laparoscopic versus conventional adrenalectomy.